Molecular characterization of high-risk human papillomaviruses in renal cell carcinoma - Ali Farhadi Andar Abi, (2013)
Renal cell carcinoma (RCC) represents five percent of adult epithelial cancers and the most prevalent malignancy of the kidney. It has been estimated that known risk factors for RCC account for less than one half of the diagnosed cases. Thus, there is a need to identify additional risk factors associated with the development of RCC. While the role of high risk human papillomavirus (HR-HPV) types in cervical, noncervical anogenital and some head and neck cancers is generally accepted by now,its oncogenic role at other anatomical sites is still debated. The aim of this study was to investigate whether HR-HPV infection is attributable to RCC or has any role in pathogenesis and development of a certain histological subtype. Formalin fixed paraffin embedded (FFPE) tissue specimens from 127 patients with histopathologically proven RCC and their respective peritumoural tissues in addition to 19 tissue control were available for this study. The presence of HPVDNA was analyzed by nested PCR assays using consensus primers (MY/GP+) primers as well as type specific primers for HPV 16/18 and sequenced for different types of HPV in case of positivity for HPV-DNA. The expression of p16INK4a, p53 and Ki-67 proteins was evaluated with the use of immunohistochemistry. Catalyzed signal-amplified colorimetric in situ hybridization (CSAC-ISH) technique was applied to demonstrate integrated and episomal viral DNA. Detection of E6/E7 oncogene transcripts of HPV 16 and 18 genotypes was performed using nested RTPCR assays. The prevalence of co-infection of HR-HPV with oncogenic viruses including Epstein–Barr virus, BK virus, JC virus or Human Herpesvirus 6 was determined as well. A retrospective analysis of clinicopathological characteristics between HR-HPV positive and HR-HPV negative RCC patients was also carried out. The HPV genome was detected in 37 (30.3%) of RCC specimens and four (4.1%) of their corresponding peritumoural tissues. HPV-18 was the most common viral type identified followed by HPV-16 and 58. The prevalence of HR-HPV infection in papillary RCC was significantly higher than other histological subtypes (p=0.007). Nuclear and/or cytoplasmic immunoexpression of p16INK4a was detected in 24 (20.3%) cases. Data analysis showed a significant correlation between p16INK4a expression and the presence of HR-HPV DNA (p<0.001). The expression pattern of the proliferation factor was correlated with the nuclear grade (p<0.001) and HPV infection (p=0.027). Chromogenic in situ hybridization analysis confirmed HR-HPV infection in 18 (45%) of RCC tumours previously tested positive for HPV-DNA. Diffuse signal pattern was identified in 15 (83.3%) samples whereas a mixed pattern of diffuse and punctate signals was only detectable in three (16.7%) cases. In addition, nested RT-PCR could detect HPV-18 spliced (E6*) and unspliced E6/E7 oncogene transcripts in five cases. In conclusion, it is proposed that human kidney tissue is susceptible to persistent HPV infections. This study indicates the association between high-risk HPV presence and renal cell carcinoma suggesting HPV infection in high-grade RCC might precede disease progression in a number of RCC tumours, particularly of papillary renal cell carcinoma subtype.